Challenges When Translating and Culturally Adapting a Measurement Instrument: The Suitability and Comprehensibility of Materials (SAM+CAM) - Catarina Wallengren; Kristina Rosengren; Richard Sawatzky; Joakim Ohlen (SAGE Publishing, 2018)
There is evidence that low suitability and comprehensibility of printed education materials (PEMs) affects patients' and relatives' ability to read and comprehend information. However, few instruments measure the suitability of written information, and none exist in the Swedish language. The aim was to describe the translation and adaptation of the Suitability and Comprehensibility of Materials (SAM+CAM) instrument into the Swedish language and health care context and to explore challenges related to this process. The SAM+CAM instrument was translated and culturally adapted in five steps: forward translation, synthesis, back translation, expert review, and pretests. Differences were found when translating and culturally adapting the SAM+CAM instrument in the areas of semantic, idiomatic, and experiences. Participants revealed several clarity inconsistencies between items. They also identified linguistic differences and unfamiliar wording; they found that the instrument was perplexing to use and lacked knowledge regarding the specific health care areas in the examined PEMs. The cultural perspective is a significant factor that influences the usability of PEMs. Therefore, expert groups of participants are useful when adapting instruments to different cultures. The Swedish SAM+CAM instrument requires experienced and highly qualified raters.